2017
DOI: 10.2196/jmir.8877
|View full text |Cite
|
Sign up to set email alerts
|

Development and Usability Evaluation of an Art and Narrative-Based Knowledge Translation Tool for Parents With a Child With Pediatric Chronic Pain: Multi-Method Study

Abstract: BackgroundChronic pain in childhood is increasingly being recognized as a significant clinical problem for children and their families. Previous research has identified that families want information about the causes of their child’s chronic pain, treatment options, and effective strategies to help their child cope with the pain. Unfortunately, parents have reported that finding this information can be challenging.ObjectiveThe aim of this study was to actively work together with children attending a pediatric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…Generally, responses from both parents and healthcare providers indicated that the videos were effective in normalizing sexual concerns and increasing perceptions of self-efficacy for coping and communication related to sexuality in the transition to parenthood. Such findings are in line with other knowledge translation tools that have been found to normalize patient experiences and consequently reduce distress (Reid et al, 2017 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Generally, responses from both parents and healthcare providers indicated that the videos were effective in normalizing sexual concerns and increasing perceptions of self-efficacy for coping and communication related to sexuality in the transition to parenthood. Such findings are in line with other knowledge translation tools that have been found to normalize patient experiences and consequently reduce distress (Reid et al, 2017 ).…”
Section: Discussionsupporting
confidence: 88%
“…Although viewers appreciated our use of racially neutral characters, one of whom was conceived to be gender-neutral, other respondents perceived the videos to be too hetero- and cis-normative. Identifying with the characters depicted in KT materials is essential to maximize impact (Lohan, Aventin, Oliffe, Han, & Bottorff, 2015 ; Reid et al, 2017 ). Consistent with shifts in the fields of sex and relationships research to prioritize inclusivity (Andersen & Zou, 2015 ), our ongoing and future research makes a concerted effort to recruit sex and gender diverse couples and our future videos will be more responsive in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Third, previous studies providing evidence for the effect of PNE in healthy children [ 10 ] and the context of pediatric pain has mainly focused on attitudes and knowledge of pain physiology, instead of pain-related outcomes such as physical functioning, pain intensity and pain-related fear [ 14 , 15 ]. Despite its frequent use in the evaluation of functional disability in the context of functional abdominal pain [ 39 , 40 ], it should be noted that the FDI was initially developed to assess perceived difficulty in a variety of activities that are relevant to children and adolescents, rather than to assess limitations specific to a particular pediatric condition such as FAPDs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The limited studies investigating PNE(-based) interventions in the pediatric chronic pain context, only include (healthy) adolescents and their parents [ 10 , 14 , 15 ]. Drawing upon available evidence in adult and adolescent samples, it is expected that PNE provided to children (6–12 years) and their parents will lead to improved pain-related outcomes in both the child and the parents.…”
Section: Introductionmentioning
confidence: 99%
“…There exists a need to ensure that practice initiatives stemming from family nursing research are sustainable, which “requires partnerships, collaboration, and strong relationships between researchers and knowledge users” (Bell, 2014, p. 8). While examples of family inclusion in end-of-grant KT are relatively absent in the literature, recent examples of unique, strengths-based approaches to KT include working with “children attending a pediatric chronic pain clinic and their parents to develop, refine, and evaluate the usability of an art and narrative-based electronic book (e-book) for pediatric chronic pain” (Reid et al, 2017, p. 1). Our example lends itself well to the budding forms of participant-led KT in family nursing research.…”
Section: Introductionmentioning
confidence: 99%